1993
DOI: 10.23986/afsci.72635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of milk fat, unhydrogenated and partially hydrogenated vegetable oils on fat metabolism of growing pigs: I. Growth, feed utilization and carcass quality in pigs fed different fats and oils

Abstract: The fatty acid composition of the dietary fats had a clear influence on the fatty acid composition of the adipose tissue of the pigs. Vegetable oils (RO and SO) increased the unsaturated fatty acid content of the adipose tissue and decreased the firmness of the backfat compared to the effects by milk fat (80, CR) (p<0,001). The correlation between linoleic acid content and firmness of back fat was significant (r=-0.83) (p<0.001). The trans fatty acid (Cl8:1) found in HSO seems to be incorporated intact into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…Similar to our results, Woodworth et al (1999) reported that 6% PF reduced ADFI and increased G/F. Soumi et al (1993) and Leskanich et al (1997) concluded that ADG increased in response to feeding diets containing a greater amount of unsaturated fat compared to more saturated fat. However, in the present studies, pigs fed CWG (minimum 61.6% unsaturated fatty acids) or PF (minimum 70.0% unsaturated fatty acids) had similar ADG.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our results, Woodworth et al (1999) reported that 6% PF reduced ADFI and increased G/F. Soumi et al (1993) and Leskanich et al (1997) concluded that ADG increased in response to feeding diets containing a greater amount of unsaturated fat compared to more saturated fat. However, in the present studies, pigs fed CWG (minimum 61.6% unsaturated fatty acids) or PF (minimum 70.0% unsaturated fatty acids) had similar ADG.…”
Section: Discussionsupporting
confidence: 89%
“…In comparing dietary fat sources, Morgan et al (1992) showed that pigs fed 5% SBO had greater ADG than pigs fed 5% beef tallow. Suomi et al (1993) and Leskanich et al (1997) also observed that ADG increased in response to feeding diets containing a greater amount of unsaturated fat compared with more saturated fat. These studies, including the current study, indicate that the difference in ADG between the SBO-and CWG-fed pigs may be partly related to dietary fatty acid composition.…”
Section: Discussionmentioning
confidence: 85%
“…The improvement in feed conversion efficiency and ADG in the pigs fed the rapeseed oil/fish oil diets could be related to the greater degree of unsaturation of these diets than of the control diet. Growth-enhancing effects of unsaturated oils have also been observed by Oldfield and Anglemier (1957) and Suomi et al (1993). The relevance of the significant effects of diet on Smokestain Reflectometer and muscle reflectance measurements is not clear.…”
Section: Discussionmentioning
confidence: 99%